EVALUASI KEBERLANJUTAN EKONOMI PERIKANAN CAKALANG DENGAN KAPAL SEKOCI PADA ZONA EKONOMI EKSKLUSIF SAMUDERA HINDIA - Nur, Andi Irwan; Boer, Mennofatria .; Bengen, Dietriech, G.; Subandar, Awal . (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2014)
A research on evaluation of economic sustainability status skipjack fisheries has been done using Rapfish estimation techniques which are simple, easy attribute to assess considering time and cost, and can be applied to various aspects of the assessment. Evaluated economic sustainability indicators are 10 attributes. Analysis result shows that all attributes are generally in unsatisfactory conditions. Other incomes sources is the most sensitive attribute for enhancing economic sustainability with root mean square value 5,36 followed by Marketable Right, Limited Entry, and. Ownership/transfer attributes with root mean square value 4,92, 4,28, and 4,18 respectively. The values of other economic attributes are relatively low ranging from 1,08 to 3, 89 indicating a slighter sensitivity. Such economic sustainability performance of the fisheries requires responsive policy interventions.